2021
DOI: 10.1101/2021.07.26.453856
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A manifold neural population code for space in hippocampal coactivity dynamics independent of place fields

Abstract: Hippocampus CA1 place cells express a spatial neural code by discharging action potentials in cell-specific locations (′place fields′), but their discharge timing is also coordinated by multiple mechanisms, suggesting an alternative ′ensemble cofiring′ neural code, potentially distinct from place fields. We compare the importance of these distinct information representation schemes for encoding environments. Using miniature microscopes, we recorded the ensemble activity of mouse CA1 principal neurons expressin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 145 publications
(315 reference statements)
0
17
0
Order By: Relevance
“…Together these finding suggest that reliable pairwise correlations, rather than simply rate modulation or temporal pattern, are the building blocks of the coding scheme employed in layer 2/3 of cortex. A similar coding scheme termed 'ensemble cofiring' has been recently proposed in area CA1 in hippocampus 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Together these finding suggest that reliable pairwise correlations, rather than simply rate modulation or temporal pattern, are the building blocks of the coding scheme employed in layer 2/3 of cortex. A similar coding scheme termed 'ensemble cofiring' has been recently proposed in area CA1 in hippocampus 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Infomax concepts are severely challenged to explain our additional observation that the cofiring relationships between simultaneously-recorded hippocampal and MEC neurons (Fig. 4C bottom) is only weakly persistent across the stable and rotating arena conditions, despite both the entorhinal (Park et al, 2019) and the hippocampal populations each exhibiting strongly persistent, attractor-like cofiring relationships (Levy et al, 2021). If MEC representations of space project to hippocampus then their discharge should be informationally coupled, and the discharge representations should be informationally coherent, perhaps even increasing in fidelity according to Infomax predictions.…”
Section: Do Signaling Games Offer Anything That Information Maximizat...mentioning
confidence: 99%
“…That is however, not to say the anti-cofiring relationships are unimportant. On the contrary, they tend to be rare, their prevalence increases with learning, and they tend to be the most important contributors to the ability to discriminate information from population network activity (Levy et al, 2021). Once established, persistent conventions tend to further increase their persistence.…”
Section: Information Asymmetric Signaling Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…Spike time correlations have been implicated in the propagation of spiking in networks (Bojanek et al, 2020; Chambers and MacLean, 2016) making them an intriguing signal when studying the circuit mechanisms and computations that give rise to behavior. Recent work has shown that spike time correlations are an informative description of visual stimuli (Dechery and MacLean, 2018; Kotekal and MacLean, 2020; Levy et al, 2020; Ruda et al, 2020), auditory stimuli (Betzel et al, 2019; Insanally et al, 2019), and spatial location (Levy et al, 2022; Nardin et al, 2021). In motor cortex (M1) pairwise spike count correlations have been shown to provide information about motor behavior beyond what is provided by firing rates alone (Maynard et al, 1999), and have also been used to improve encoding models that predict the activity of neurons (Stevenson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%